LEGAL CERTAINTY OF INFORMED CONSENT IN HIGH-RISK TOOTH EXTRACTION: AN INDONESIAN HEALTH LAW PERSPECTIVE - Evi Imelda Pelawi; Irsyam Risdawati; Sidi, Redyanto (International Journal of Synergy in Law, Criminal, and Justice, 2025)
This study discusses the legal certainty of informed consent in high-risk tooth extraction from the perspective of health law in Indonesia. Informed consent is a key element in medical practice that guarantees the patient's right to obtain clear and adequate information before undergoing medical treatment and protects doctors from allegations of malpractice. In the context of tooth extraction performed in an emergency, the legal certainty of informed consent is very important to protect patient rights and provide legal protection for dentists. This study was conducted at the independent practice of drg. Evi Imelda Pelawi - Dental Care located in Simalungun, North Sumatra, where it was found that many patients still do not prioritize the importance of informed consent. The results of the study indicate that dentists can be free from malpractice claims as long as they have provided adequate explanations in accordance with Article 7 of the Regulation of the Minister of Health Number 290/Menkes/Per/III/2008 and the patient or family has signed an informed consent as proof of agreement. However, this study also found weaknesses in the regulation related to the provisions on time recording which are not regulated in detail, thus potentially weakening legal evidence in the event of a dispute. Therefore, this study recommends that the regulation be updated to strengthen legal certainty in medical practice, especially in high-risk tooth extraction procedures in independent practices.